Social and economic impacts of Maritime Automated Surface Ships - Björk, Eric (My University, 2021)
With the dawn of maritime autonomous surface ships, more and more development projects aimed at utilizing and exploring the possibilities of autonomous AI driven vessels have begun. There are several innovation projects from the industry that explore the potential, suitability and benefits of autonomous ships. These include, slow steaming, fuel efficiency, new propulsion options, new vessel design, and technologies to aid in the navigation and traffic coordination of vessels. While these technological advances are indeed important and challenging, there is little work on the effects of this transition on social and economic elements such as vocational competencies and skillsets and how task and job descriptions will evolve. Recently the reality of these types of ships has been made apparent. Projects such as MAXCMAS (Queen's University Belfast, 2018)have shown that the autonomous ships are capable of following COLREGs (International Maritime Organization, 2003) just as well as, if not better, than humans. The IMO is looking into implementing amendments for autonomous ships into their instruments (International Maritime Organization, 2018, 2019). Amidst the technological advancements there exists uncertainty, fears of losing jobs, livelihoods and being ¨left behind¨ by the developing technology. This study explores what impact we can expect on the shipping industry by digitalization and automation. Specifically, those who are part of the operations surrounding and within the merchant fleet. The study also discusses what the most desirable skillsets for the industry could be in the future. An extensive literature search together with interviews and data from popular media form the main basis for this thesis. Low-skill and medium-skill groups are at the highest likelihood of automation with a large part of the jobs tasks being possible to be replaced by automated functions in the future, and that the change is expected to be evolutionary rather than revolutionary. Another finding is that highly routine tasks (whichever skill level they belong to) are most apt to automate, be they cognitive or manual while non-routine tasks would be less likely to soon be automated. Skillsets that face the highest demand in the future appear to be belonging to the cognitive and social categories. When it comes to the economic impact from shifting to autonomous ships we can see that the change also could facilitates new technology. The ships type could benefit from less moving parts and thus also from alternative types of propulsion or energy sources, especially if unmanned. This could facilitate for greener options that use energy which doesn’t require combustion. The results from this study show that highly autonomous vessels will most likely not be a radical game changer in terms of impacting employment for the nearest decades. The scope of the deployment of the autonomous vessels will most likely be limited to domestic trades by 2040, with some of the autonomous benefits being applied to other vessels for decision-making support.
Keywords: Maritime shipping; Levels of automation; Disruptive technologies; Social and economic change; Maritime management